Frequent detection of functional hyposplenism via assessment of pitted erythrocytes in patients with advanced liver cirrhosis. - Malte H Wehmeyer; Harsha Sekhri; Raluca Wroblewski; Antonio Galante; Thomas Meyer; Ansgar W Lohse; Julian Schulze Zur Wiesch (PLoS ONE)
Background Asplenia or functional hyposplenism are risk factors for severe infections, and vaccinations against encapsulated bacteria are advised. There are only limited data regarding the spleen function of cirrhotic patients. Methods We evaluated spleen function in patients with liver cirrhosis, who were prospectively enrolled in this study. Spleen function was evaluated by the measurement of pitted erythrocytes. Functional hyposplenism was defined as a percentage of PE of >15%. Results 117 patients, mean age 58.4 years and 61.5% (n = 72) male with liver cirrhosis were included. Functional hyposplenism was diagnosed in 28/117 patients (23.9%). Pitted erythrocytes correlated with albumin (p = 0.024), bilirubin (p<0.001), international normalized ratio (INR; p = 0.004), model of end-stage liver disease (MELD) score (p<0.001) and liver stiffness (p = 0.011). Patients with functional hyposplenism had higher MELD scores (median 13 vs. 10; p = 0.021), liver stiffness (46.4 kPa vs. 26.3 kPa; p = 0.011), INR (1.3 vs. 1.2; p = 0.008) and a higher Child-Pugh stage (Child C in 32.1% vs. 11.2%; p = 0.019) as compared to patients without functional hyposplenism. Functional hyposplenism was not associated with the etiology of cirrhosis. Importantly, 9/19 patients with Child C cirrhosis had functional hyposplenism. Conclusion A quarter of patients with liver cirrhosis and almost 50% of patients with Child C cirrhosis have functional hyposplenism. Functional hyposplenism is associated with poor liver function and the degree of portal hypertension, which is characterized by higher liver stiffness measurements in transient elastography.